Persistence and dynamic of forest snails in the Western Carpathians over the last 40 thousand years - Juřičková, Lucie; Horáčková, Jitka; Horsáková, Veronika; Hájková, Petra; Hošek, Jan; Horsák, Michal (Boreas, 2025)
The glacial/interglacial cycles have shaped the landscape of temperate Europe for the past 2.5 million years, with open landscapes prevailing during the glacial and forested landscapes during the interglacial periods. However, the survival and recolonization strategies of temperate forest species during glacial phases remain poorly understood and hotly debated. This study investigates the persistence and postglacial dispersal of forest molluscs in the Western Carpathians by analysing molluscs from 126 Last Glacial and Early Holocene sites. Radiocarbon dating was applied to directly date shells of the target forest species, minimizing the risk of contamination from colluvial sediments. Our results confirm the presence of 15 forest snails in 33 sites in the region for the last 44 ka, with evidence of five species surviving the MIS 2. These findings support the hypothesis of localized microrefugia in the Western Carpathians, which allowed forest species to persist during unfavourable climatic conditions and facilitated their recolonization in the Holocene. In addition, our study highlights considerable temporal variation in mollusc successional patterns, with a sharp increase in forest species during the post‐Last Glacial Maximum period. Despite these advances, the exact location of glacial (micro)refugia remains unclear for many species, highlighting the need for further research. This study provides new insights into the complex biogeographical history of forest molluscs in temperate Europe, emphasizing the need for high‐resolution dating techniques and extensive sampling to accurately reconstruct past environmental changes.